2017
DOI: 10.1523/jneurosci.3046-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

An Agonist of the Protective Factor SIRT1 Improves Functional Recovery and Promotes Neuronal Survival by Attenuating Inflammation after Spinal Cord Injury

Abstract: Targeting posttraumatic inflammation is crucial for improving locomotor function. SIRT1 has been shown to play a critical role in disease processes such as hepatic inflammation, rheumatoid arthritis, and acute lung inflammation by regulating inflammation. However, the role of SIRT1 in spinal cord injury (SCI) is unknown. We hypothesized that SIRT1 plays an important role in improving locomotor function after SCI by regulating neuroinflammation. In this study, we investigate the effect of SIRT1 in SCI using pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 92 publications
2
51
0
Order By: Relevance
“…It is documented that SIRT1 is critically involved in variable cell biological function . Loss of SIRT1 in SIRT1 knock‐out mice delayed locomotor recovery, in association with more expression of pro‐inflammatory cytokines and population of M1 type macrophages in a mouse model with spinal cord injury . Consistent with the previous report, we observed that Res up‐regulated the expression of SIRT1, whereas LPS moderately reduced the expression of SIRT1 in BMDMs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is documented that SIRT1 is critically involved in variable cell biological function . Loss of SIRT1 in SIRT1 knock‐out mice delayed locomotor recovery, in association with more expression of pro‐inflammatory cytokines and population of M1 type macrophages in a mouse model with spinal cord injury . Consistent with the previous report, we observed that Res up‐regulated the expression of SIRT1, whereas LPS moderately reduced the expression of SIRT1 in BMDMs.…”
Section: Discussionsupporting
confidence: 90%
“…[22][23][24] Loss of SIRT1 in SIRT1 knock-out mice delayed locomotor recovery, in association with more expression of pro-inflammatory cytokines and population of M1 type macrophages in a mouse model with spinal cord injury. 25 Consistent with the previous report, 22 we observed that Res up-regulated the expression of SIRT1, whereas LPS moderately reduced the expression of SIRT1 in BMDMs. The results were consistent with previously reports, in which there was lower SIRT1 expression in the inflammatory lungs of animal models with LPS-induced ALI and pulmonary contusion.…”
Section: Res Suppressed M1 Cell-biased Polarization Of Bmdms From Wsupporting
confidence: 92%
“…SCI is a neurological disease that is commonly caused by traumatic events on the spinal cords [2,3]. Based on previous results derived from studies using animal models of SCI, the pathogenesis of SCI can be divided into the primary mechanical injury, and secondary damage that are characterized by various pathophysiologic mechanisms including oxidative stress [4], mitochondrial dysfunction [5] and inflammation [6]. The prognosis of SCI is significantly poor and could lead to permanent movement disorders and cognition impairment or even paralysis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol promotes M1-to-M2 plasticity and M1 cell death in murine and human MF by a mechanism involving Arg1 activation (53,177,250,292); however, it has controversially been reported that resveratrol inhibits TAM M2 polarization observed in vivo in mice (323). Synthetic SIRT1-activating compounds have been developed: They have a greater potency compared with resveratrol; among them, SRT1720 has an anti-inflammatory effect that acts by reducing the number of M1 in mice (44,48). The SIRT3 activator Honokiol inhibits iNOS expression, NF-jB and TNFa secretion in LPS-stimulated murine MF (39).…”
Section: Manipulating the Metabolism To Polarize Mfmentioning
confidence: 99%